Les réalisations du pouvoir soviétique 1917 - 1957. (Paris : Etudes Soviétiques, 1957)
Bibliotheek Camille Huysmans
Supplement van 'Etudes Soviétiques', nr. 118
Frans
Monografie
Keywords: Sovjet-Unie.